The collective eaudiobook A novel. - Gaylin, Alison (HarperAudio, 2021)
""Chilling...this terrific novel is...propelled by an iron-tight plot that becomes increasingly tense."" —New York Times Book Review ""It's a nerve-shredding, emotionally harrowing ride. Don't miss it." —Megan Abbott, New York Times bestselling author The USA Today bestselling and Edgar Award–winning author of Never Look Back and If I Die Tonight asks how far a grieving mother will go to right a tragic wrong in this propulsive novel of psychological suspense. Camille Gardener is a grieving—and angry—mother who, five years after her daughter's death, is still obsessed with the privileged young man she believes to be responsible. When her rash actions draw the attention of a secret group of women—the collective— Camille is drawn into a dark web where these mothers share their wildly different stories of loss as well as their desire for justice in a world where privilege denies accountability. Fueled by mutual rage, the collective members devise and act out retribution fantasies via precise, anonymous, highly coordinated revenge killings. As Camille struggles to comprehend whether this is a role-playing exercise or terrifying reality, she must decide if these women are truly avenging angels or monsters. Becoming more deeply enmeshed in the group, Camille learns truths about the collective—and about herself—that she may not be able to survive